INDUSTRI RUMAHAN MAKANAN TRADISIONAL DAKAK-DAKAK DI NAGARI SIMABUR KECAMATAN PARIANGAN KABUPATEN TANAH DATAR PROVINSI SUMATERA BARAT - Ahda Adila; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This purpose research to know social capital on the development industry of dakak-dakak and obstacle on the development industry of dakak-dakak. This research implementation in the Simabur Village Pariangan District Tanah Datar Regency West Sumatra Province. Subjects in this research is 5 people dakak-dakak of entrepreneur in the Simabur Village Pariangan District. Technique used in this research is purposive sampling technique. Purposive sampling is taking the subject of research done on porpose, pengambilan subjek penelitian yang dilakukan dengan sengaja, which in accordance whit the requirements of informants in need. The method used is a qualitative research method because this method explain any concerns regarding this tittle is descriptive. Instrument data filtering is observation, questionnaires and documents. The theory used is the theory of social capital where in there are trust, social of net, and value and norm. The result were made public in the field that social capital on development dakak-dakak of industry is there are trust of happened between entrepreneur of dakak-dakak and buyer on the made dakak-dakak, there are social of net in the form of social of relationship on the shape cooperation happened between entrepreneur of dakak-dakak and buyer on the marketing of dakak-dakak, there are value and norm in the form of feel another price and respect between entrepreneur of dakak-dakak and buyer on the development industry of dakak-dakak, and there are obstacle on the development industry of dakak-dakak in the form obstacle on the search standard material rice and gas, obstacle on the marketing, obstacle on the borrow of money to effort of dakak-dakak, and ever experienced loss on the effort of dakak-dakak. Keywords : Social Capital, Industry of Dakak-Dakak, Entrepreneour of Dakak-